Biological potential and in vitro study of the digestion of soluble peptides of different varieties of cheese - Moreira, Keila; Santos, Wellington; Silva, Euzanyr; Silva, Maria Emilia; Silva, Edson (Pubvet, 2019)
CCurrently, the concern with quality of life has raised the consumption of health food promoters, and therefore, research in search of natural compounds that exercise biological activity have intensified in the last decade. The objective was to evaluate the antioxidant activities, chelating Fe2+ and Cu2+ ions, antihypertensive proteins and water-soluble peptides of buffalo and bovine rennet cheeses, gorgonzola, mozzarella, cheddar and ricotta. The antioxidant activities were performed using the radicals ABTS+ • (2,2'-azinobis-3-ethylbenzothiazoline-6-sulphonic acid) and DPPH (2,2-diphenyl-1-picrylhydrazyl), Fe2+ and Cu2+ ions were used for chelating activity and the substrate FAPGG (N- [3- (2-furyl) acryloyl] -L-phenylalanine-glycyl-glycine) was used to evaluate the inhibition of angiotensin converting enzyme. The water-soluble proteins and peptides from the different varieties of cheese had the capacity to eliminate ABTS+ • and DPPH• radicals higher than 50% and 80%, respectively. The chelation of the Fe2+ and Cu2+ ions occurred between 1% and 70%, depending on the type of cheese. The ACE inhibitory potential of the aqueous extracts containing the small protein fragments is between 8% and 50% before and after the action of the enzymes of the gastrointestinal tract. Thus, the cheeses analyzed have the potential to be used as functional foods due to the biological multifunctionality presented by proteins and peptides extracted.
Keywords: antihypertensive; antioxidante; bioactivepeptides; functionalfood